Student empowerment and development through note-taking in one-to-one sessions - Grierson, Heather; O'Hatnick, Joannah (Journal of Learning Development in Higher Education, 2025)
This study was prompted by a senior management request at the authors’ university to change record keeping practices. What followed was an exploration of the theoretical foundations that underpin the authors’ underlying philosophy on case notes as a means for advancing student empowerment. Findings revealed that through the application of reflective practice, case notes could enhance student empowerment and development. Without reflection, however, case notes were more likely to follow the medical model in which they were ‘norm referenced and deficit driven’ (Cheek and Rudge, 1994, p.42). Co-authored, cloud-based case notes had the power to embody the ‘person-centred, emancipatory values’ (Webster, 2023, p.2) espoused by ALDinHE and ICALLD partner organisations such as AALL. These case notes were found to have changed the dynamic between student and learning developer; students had greater agency both during and after the session to interpret, adapt, and reflect upon their experiences. The new practices enhanced inclusivity by emphasising a strengths-based approach and by reducing students’ cognitive and emotional barriers. The ALDcon25 workshop explored how expanded notions of accessibility, equity, and inclusivity could change practices in one-to-one (1-2-1) sessions. Drawing upon the theories of self-regulated learning (Chickering and Reisser, 1993; Zimmerman, 2015) and critical pedagogy (Freire, 2018) that inform the authors’ practices, the session shared key elements of literature review, survey results, and findings on case note practices. An interesting highlight was the intersections and disjunctions between theory and practice. Participants were encouraged to discuss best practices to enhance student empowerment during the session with a view to leave with tangible ideas to implement in their respective work.